The impact of parental co-parenting on relational aggression in adolescents: the mediating role of peer relationships and self-control - Yongzhi Jiang; Yongzhi Jiang; Huizhe Wang; Lifang Tong (Frontiers in Psychology)
PurposeTo explore the impact of parental co-parenting on adolescents’ relational aggression, as well as the mediating roles of peer relationships and self-control.MethodA self-reported questionnaire survey was conducted on 550 students from three junior high schools in Inner Mongolia using the Parental Coordinated Parenting Scale, Relational Aggression Scale, Self-Control Scale, and Peer Relationship Scale.ResultPositive parental co-parenting is significantly negatively correlated with relational aggression, while negative co-parenting is significantly positively correlated with relational aggression. Positive co-parenting is significantly positively correlated with peer relationships and self-control, while negative parental co-parenting is significantly negatively correlated with peer relationships and self-control. Relational aggression is significantly negatively correlated with peer relationships and self-control, and peer relationships are significantly positively correlated with self-control. The direct effect of negative parental co-parenting on relational aggression is significant, and self-control, peer relationships, and the mediating effects of peer relationships and self-control in the relationship between parental co-parenting and relational aggression are all significant.ConclusionParental co-parenting not only directly affects adolescents’ relational aggression but can also indirectly influence relational aggression through the mediating effects of peer relationships and self-control.